Linking tourists’ and micro-entrepreneurs’ perceptions of souvenirs: The case of Fiji - Kumar, N.; Trupp, Alexander *; Pratt, S. (Routledge, 2022)
Most tourists return home with a souvenir purchased after a holiday. Studies on souvenirs have mainly focussed on either the demand or supply perspective. This research integrates both perspectives to achieve a more holistic understanding of souvenirs in the Pacific context. This paper compares souvenir purchase behaviour of cruise ship visitors and overnight tourists. The research also examines the main reasons micro-entrepreneurs sell souvenirs and the meanings they attach to souvenirs. Overnight tourists have a deeper understanding and appreciation for souvenirs compared to cruise ship visitors. Suppliers provide souvenirs to sustain their culture, as well as for economic reasons.